1973
DOI: 10.1002/pol.1973.180111113
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 spin‐lattice relaxation study of linear polymers in solution

Abstract: Proton‐decoupled, partially relaxed, Fourier‐transform NMR of 13C in natural abundance was used to determine spin‐lattice relaxation times of individual carbons of polyisobutylene, polyacrylonitrile, poly(vinyl chloride), and poly(vinyl alcohol) in solution. It is shown that the relaxation times are independent of the difference in stereochemical configuration. From the values of the nuclear Overhauser enhancement factor it is shown that the relaxation times are independent of the difference in stereochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1975
1975
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 24 publications
(4 reference statements)
1
21
0
1
Order By: Relevance
“…These experiments measure the activation energy of the spin-lattice relaxation time T 1 which is related to the sum of the activation energy of the local process E loc and that of the viscosity E η : E T1 ) E loc + E η . From such an evaluation of T 1 experiments Dejean de la Batie et al 8 found E loc ) 5 kcal/mol for PIB in chloroform, while Jones et al 9 and Inoue et al 10 This data array fits the upper range of the rotational barriers of the hydrocarbons which are found typically between 3 e E e 3.5 kcal/mol. The value of 3.1 kcal/ mol for the activation energy of τ 0 resulting from the intrachain viscosity analysis of our PIB/toluene data is …”
Section: Analysis and Discussionmentioning
confidence: 85%
“…These experiments measure the activation energy of the spin-lattice relaxation time T 1 which is related to the sum of the activation energy of the local process E loc and that of the viscosity E η : E T1 ) E loc + E η . From such an evaluation of T 1 experiments Dejean de la Batie et al 8 found E loc ) 5 kcal/mol for PIB in chloroform, while Jones et al 9 and Inoue et al 10 This data array fits the upper range of the rotational barriers of the hydrocarbons which are found typically between 3 e E e 3.5 kcal/mol. The value of 3.1 kcal/ mol for the activation energy of τ 0 resulting from the intrachain viscosity analysis of our PIB/toluene data is …”
Section: Analysis and Discussionmentioning
confidence: 85%
“…glass tubes and were not degassed since the relaxation times of the polymer are not substantially affected by the presence of dissolved oxygen, at least at atmospheric pressure. 14 The solvents used were toluene-d8 and cyclohexane-d12, both obtained from E. Merck A.G. The polymer concentration was 15% (wt/vol).…”
Section: Methodsmentioning
confidence: 99%
“…Mitani (28) found no deviation from Bernoullian statistics but Pham (27) and Adel-Alim (26) found it non-Bernoullian outside the 30° -50° range of polymerization temperature. Inoue (29) has shown that the spin-lattice relaxation time T 1 of 1 3c is the same irrespective of the tactic configuration and of the molecular weight, so the intensities of the observed 13c resonances are directly related to the real concentration of carbon atoms in each configuration as for instance for-the tetrads measured by Carman (30). Since the syndiotactic index measuredfor diadie placement is 0.54-0.56 for industrial PVC (0.50 is the purely atactic random case) the probabili ty of only five syndiotactic successive lllac_ements ( six m.u.)…”
Section: Short Branchesmentioning
confidence: 99%